DIFFERENCES OF PHYSIOLOGICAL PARAMETERS AND SUCROSE METABOLISM IN BREAD WHEAT GENOTYPES EXPOSED TO DROUGHT STRESS - İ. Kutlu; E. Turhan; Ö. Yorgancilar; A. Yorgancilar (Journal of Animal and Plant Sciences, 2020)
Twelve bread wheat genotypes were assessed for physiological parameters and sucrose metabolism for genotypic variations under drought stress condition. The field experiments were conducted 2013–2014 under irrigated and rain-fed conditions (having extremely dry conditions) to investigate the flag leaf area (FLA), flag leaf chlorophyll content (Chl), relative water content (RWC), loss of turgidity (LT), sucrose content, reducing sugars content, starch content, acid invertase activity (INV) and sucrose synthase activity (SS) in wheat genotypes. Although FLA, Chl, RWC and starch content decreased in all genotypes under drought conditions, LT generally increased, whereas sucrose content, reducing sugars content, acid INV and SS activities varied from genotype to genotype. Based on the results of Chl, RWC, and LT genotypes DH16, DH19 and Kate A-1 were relatively drought-tolerant genotypes. In addition, the genotypes DH16, DH18, DH19, Krasunia-Odeska and Syrena-Odeska adjusted their sucrose metabolism well when exposed to drought stress. Moreover, the genotypes DH19, DH21, Bezostaja-1 and Krasunia-Odeska regulated acid INV activity. The results suggest that Chl, water status of the leaves, reducing sugars and acid INV activity could be an effective selection criteria of drought tolerance for wheat.
Keywords: Acid invertase; soluble sugar; sucrose synthase; Triticum aestivum L.; water deficit